Administration of Intravenous Iron Formulations Induces Complement Activation in-vivo - Faria, Bernardo; Gaya da Costa, Mariana; Poppelaars, Felix; Franssen, Casper F. M.; Pestana, Manuel; Berger, Stefan P.; Daha, Mohamed R.; Gaillard, Carlo A. J. M.; Seelen, Marc A. (Frontiers in Immunology, 2019)
Background: Intravenous (IV) iron is widely used to treat anemia in chronic kidney disease patients. Previously, iron formulations were shown to induce immune activation in-vitro. The current study aimed to investigate the effect of IV iron on complement activation in-vivo, and whether this subsequently induces inflammation and/or oxidative stress. Methods: Two distinct patient groups were included: 51 non-dialysis and 32 dialysis patients. The non-dialysis group received iron sucrose or ferric carboxymaltose, based on physicians' choice. Plasma samples were collected prior to and one hour after completion of IV iron infusion. The dialysis group received iron sucrose exclusively. Plasma samples were collected at the start and end of two consecutive hemodialysis sessions, one with and one without IV iron. Finally, plasma levels of MBL, C1q, properdin, factor D, sC5b-9, MPO, PTX3 were assessed by ELISA. Results: In the non-dialysis group, sC5b-9 levels significantly increased after IV iron by 32%, while levels of factor D and MBL significantly dropped. Subgroup analysis demonstrated that iron sucrose induced complement activation whereas ferric carboxymaltose did not. In the dialysis group, levels of sC5b-9 significantly increased by 46% during the dialysis session with IV iron, while factor D levels significantly fell. Furthermore, the relative decrease in factor D by IV iron correlated significantly with the relative increase in sC5b-9 by IV iron. MPO levels rose significantly during the dialysis session with IV iron, but not in the session without iron. Moreover, the relative increase in MPO and sC5b-9 by IV iron correlated significantly. PTX3 levels were not affected by IV iron. Conclusions: Iron sucrose but not ferric carboxymaltose, results in complement activation possibly via the lectin and alternative pathway partially mediating oxidative stress but not inflammation.